A novel mechanism of monoethylhexyl phthalate in lipid accumulation via inhibiting fatty acid beta-oxidation on hepatic cells - Xu, Tengfei (2022)
Monoethylhexyl phthalate (MEHP) is one of the main active metabolites of the plasticizer di(2-ethylhexyl) phthalate. It has been known that MEHP has an impact on lipolysis; however, its mechanism on the cellular lipid metabolism remains largely unclear. Here, we first utilized global lipid profiling to fully characterize the lipid synthesis and degradation pathways upon MEHP treatment on hepatic cells. Meanwhile, we further identified the possible MEHP-targeted proteins in living cells using the cellular thermal shift assay (CETSA) method. The lipidomics results showed that there was a significant accumulation of fatty acids and other lipids in the cell. The CETSA identified 18 proteins and fatty acid β-oxidation inhibition pathways that were significantly perturbed. MEHP's binding with selected proteins HADH and HSD17B10 was further evaluated using molecule docking, and results showed that MEHP has higher affinities as compared to endogenous substrates, which was further experimentally confirmed in the surface plasma resonance interaction assay. In summary, we found a novel mechanism for MEHP-induced lipid accumulation, which was probably due to its inhibitive effects on the enzymes in fatty acid β-oxidation. This mechanism substantiates the public concerns on the high exposure level to plasticizers and their possible role as an obesogen.